A Systematic Review of Geothermal-Solar Hybrid Systems: Design, Performance, Operational Advantages, and Configuration Principles - Richard Wempie Vicky Uguy; Estrela Bellia Muaja (International Journal Science and Technology, 2025)
Indonesia’s dependence on fossil fuels has resulted in significant environmental degradation and contributes to rising CO₂ emissions, despite the country’s vast renewable energy potential. Geothermal and solar energy, as two of the most promising clean energy sources, offer complementary characteristics that can be leveraged in hybrid power systems. This study aims to identify optimal configuration strategies for hybrid geothermal–solar systems and evaluate their operational advantages over standalone geothermal plants in the Indonesian context. Employing a Systematic Literature Review (SLR) approach, this research synthesizes findings from recent literature (2012–2024) across major scientific databases. The review focuses on system design, working principles, thermodynamic performance, and implementation feasibility. Results show that preheating/superheating configurations using solar input can significantly enhance geothermal plant efficiency, increase brine enthalpy, and reduce scaling issues—common challenges in Indonesian geothermal operations. Hybrid systems demonstrate an average efficiency gain of 3–7% over conventional configurations. While these systems offer improved reliability, flexibility, and land use optimization, they also involve technical complexity and high capital costs. This study underscores the potential of geothermal–solar hybrid systems to support Indonesia’s clean energy transition by increasing plant efficiency, reducing emissions, and optimizing renewable resource utilization.